The possibility of using anti-human monoclonal antibody CD3 as pan T-cell marker in guinea pigs - Popko, S. S.; Aksamytieva, M. V.; Попко, Світлана Сергіївна; Аксамитьєва, Марія Володимирівна (My University, 2022)
The present study was aimed to evaluate the possibility of using anti-human monoclonal antibody CD3 as pan T-cell marker in the guinea pigs’ trachea and lung in early and late manifestations of the allergic inflammatory process. Materials and methods.We have studied the distribution and quantitative changes of CD3-positive lymphocytes in trachea and lung of guinea pigs using histological, immunohistochemical, statistical methods in conditions of experimental inflammatory process. Results. Our results revealed the applicability of anti-Human monoclonal antibody CD3 (Clone SP7, «DAKO», Denmark) cross-reaction with T-cells of guinea pigs’ tracheas and lungs. The most statistically significant elevation of the number of CD3-positive lymphocytes, in comparison with the control group (p*/** < 0.05), observed in the experimental group III in the late stages of experimental inflammatory process. The elevation of the number of CD3-positive lymphocytes persists even after the termination of the allergen action, which indicates the continuation of the reaction of pulmonary local adaptive immunity to the allergen. Conclusions. The results of our study may be useful in conditions of the deficiency of guinea pig-specific tests. The immunohistochemical assessment of guinea pigs’ trachea and lungs proved the possibility to use anti-Human monoclonal antibody CD3 as a panT-cell marker in guinea pigs. We demonstrated the activation of adaptive immune response (T-cells), represented by their immunohistochemical changes, predominantly in the late stages of experimental inflammatory process.
Keywords: experimental inflammation; CD3; guinea pig; lung; trachea